Penyesuaian Diri Penyandang Low Vision dalam Melewati Pendidikan di Perguruan Tinggi - Tommy Hari Firmanda (Jurnal Psikologi Tabularasa, 2014)
This study aimed to know adjusment of college students with low vision. This study used a qualitative approach with case study method. Data were obtained through interviews with five students with low vision who are undergoing the process of education in college. The data were analyzed thematically and use coding of the verbatim record from the interview. Strengthening the credibility of the research conducted by use investigator triangulation and checking by peers through discussion. Based on the analysis results obtained five main themes. These themes describe problems faced by Persons with low vision in the university campuses, Academic Adjustment in the university, Social Adjustment in the university, Adjustment Strategies used by persons with low vision to Solve Learning Problems in the university, and Factors Affecting Persons with low vision Academic success in Higher Education.